Echographic and physical characterization of albumin-stabilized nanobubbles. Issue 6 (June 2019) - Watanabe, Akiko; Sheng, Hong; Endo, Hitomi; Feril, Loreto B.; Irie, Yutaka; Ogawa, Koichi; Moosavi-Nejad, Seyedeh; Tachibana, Katsuro
Abstract: There has been increasing interest in using nanobubbles (NBs) for ultrasound mediated drug delivery as well as for ultrasound imaging. Albumin NBs are especially attractive for its potential of becoming a versatile platform for drug carriers and molecular targeted therapy agents. However, physical characterization of NBs is generally considered to be difficult due to various technical issues, such as concentration limitations, nanoparticle contamination, etc. In the present study, we measured the size distribution, concentration and weight density of albumin stabilized NBs by means of multiple nanoscale measurement modalities. Laser nanoparticle tracking analysis, multicolor flow cytometry, resonance mass evaluation showed consistent measurement results of the NBs with low mass weight density and diameter size ranging from 100 nm to 400 nm. Furthermore, the NB solution showed excellent images by high frequency ultrasound (30–50 MHz) in flow model acoustic phantoms. The NBs also induced acute cell disruption by low intensity ultrasound (0.8 W/cm 2 ) irradiation. We successfully fabricated and characterized albumin stabilized NBs which could serve as an effective platform for future theranositic agents.